The impact of foreign large-scale land acquisitions on smallholder productivity: Evidence from Zambia - Sipangule, Kacana; Lay, Jann (International Food Policy Research Institute, 2015)
In light of the surge of foreign large-scale land acquisitions (LSLA) in developing countries, concerns have been raised that large-scale agricultural projects could negatively affect smallholder livelihoods. There is, however, very little evidence beyond case studies that support these claims. Drawing on nationally representative household datasets from 2000 and 2010, as well as an inventory of foreign LSLA from Zambia, this study investigates the impacts of foreign LSLA on the productivity, fertilizer use, and wage-employment opportunities of smallholders. Using a difference-in-difference approach, we find that smallholders located in districts with foreign LSLA are not worse off than smallholders in districts without foreign LSLA. Instead, we find consistent evidence of a convergence in the productivity levels of smallholders in districts with and without foreign LSLA. Our results allow for the careful conclusion that LSLA, despite being of considerable magnitude in Zambia, have not had any disruptive effects on the smallholder economy at the district level.